Disharmonization Of Regional Regulation Of Samarinda Number 2 Of 2019 On State Land Clearing Permit: Disharmonisasi Peraturan Daerah Kota Samarinda Nomor 2 Tahun 2019 Tentang Izin Membuka Tanah Negara - helmi, Muhammad Helmi (Badan Perencanaan Pembangunan Daerah, Penelitian dan Pengembangan Kota Samarinda, 2025)
In the land sector, this is a central government authority that is delegated to the regions. Does the local government have complete or partial authority?. This research is normative with a legislative and comparative approach. The results of the study are disharmonization in the IMTN Regional Regulation of Samarinda City, where the phrase